Safety and PCR monitoring in 161 semi-immune Kenyan adults following controlled human malaria infection - Kapulu, MC; Njuguna, P; Hamaluba, M; Kimani, D; Ngoi, JM; Musembi, J; Ngoto, O; Otieno, E; Billingsley, PF (American Society for Clinical Investigation, 2021)
BACKGROUND. Naturally acquired immunity to malaria is incompletely understood. We used controlled human malaria infection (CHMI) to study the impact of past exposure on malaria in Kenyan adults in relation to infection with a non-Kenyan parasite strain. METHODS. We administered 3.2 × 103 aseptic, purified, cryopreserved Plasmodium falciparum sporozoites (Sanaria PfSPZ Challenge, NF54 West African strain) by direct venous inoculation and undertook clinical monitoring and serial quantitative PCR (qPCR) of the 18S ribosomal RNA gene. The study endpoint was met when parasitemia reached 500 or more parasites per μL blood, clinically important symptoms were seen, or at 21 days after inoculation. All volunteers received antimalarial drug treatment upon meeting the endpoint. RESULTS. One hundred and sixty-one volunteers underwent CHMI between August 4, 2016, and February 14, 2018. CHMI was well tolerated, with no severe or serious adverse events. Nineteen volunteers (11.8%) were excluded from the analysis based on detection of antimalarial drugs above the minimal inhibitory concentration or parasites genotyped as non-NF54. Of the 142 volunteers who were eligible for analysis, 26 (18.3%) had febrile symptoms and were treated; 30 (21.1%) reached 500 or more parasites per μL and were treated; 53 (37.3%) had parasitemia without meeting thresholds for treatment; and 33 (23.2%) remained qPCR negative. CONCLUSION. We found that past exposure to malaria, as evidenced by location of residence, in some Kenyan adults can completely suppress in vivo growth of a parasite strain originating from outside Kenya. TRIAL REGISTRATION. ClinicalTrials.gov NCT02739763. FUNDING. Wellcome Trust.